Three-dimensional Image Segmentation using Tissue-like P System - Yahya, Salah I.; Yahya, Rafaa I.; Al-Salibi, Bisan; Al-Khafaji, Ghada K.; Shamsuddin, Siti Mariyam (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
Membrane computing (MC), which abstracts computational models from the structure and functioning of biological cells or population of cells in tissues, has served as a rich framework for handling many problems. Various types of P systems have been proposed in the literature to perform edge-based and region-based segmentation of two-dimensional digital images. However, less attention has been paid to the segmentation of three-dimensional (3D) medical images. Hence, the main contribution of this paper is to propose a tissue-like P system for segmenting 3D medical images. To the best of our knowledge, this is the first work that practically adapts MC for 3D images. Experimental results demonstrate the efficiency of the proposed approach in segmenting 3D images, and it has the potential to be used in real-world applications.